Equivalente de dose pessoal Hp(10) no diagnóstico por imagem utilizando detectores OSL baseados na fluorita brasileira - Pagotto, Ivan (2021)
Ionizing radiation has applications in many different areas, ranging from health to services. Although they are fundamental to human activity, they can lead to unwanted biological effects on living beings and the environment. Currently, occupationally exposed individuals, according to the International Labor Organization and current national standards, must be monitored by monitoring services accredited by regulatory bodies, in the case of Brazil, by the National Nuclear Energy Commission. External individual monitoring takes place through operational quantities evaluated in Brazil through passive dosimetry with the use of individual monitors or dosimeters. The passive dosimeter can be composed of one or more sensitive detector elements, attenuating filters and packages suitable for routine work. Among the most used materials for personal dosimetry are thermoluminescent (TL) detectors based on lithium fluoride (LiF) and optically stimulated luminescence (Optically Stimulated Luminescence) based on aluminum oxide doped with carbon (Al2O3:C). OSL detectors have several advantages over TL, which has led to a search for new OSL materials and processes associated with their application. In particular, fluorite ore composed basically of calcium fluoride (CaF2) has stood out in the latter for dosimetric applications. In view of its availability in Brazil and accessibility, in this work an algorithm was developed to assess the personal dose equivalent Hp(10) with the OSL technique for photon energy range applied in imaging diagnosis based on Brazilian national fluorite. The algorithm developed part of the computerized deconvolution of the OSL intensity signal to apply the conversion and correction factors that vary with the material’s energy response. The results of blind tests with the algorithm in this work indicate that it is possible to evaluate such factors from the OSL emission curves of CaF2 detectors for photon energies between 30 and 150 keV, satisfying the criterion of the trumpet curve for individual monitoring. For application with other types and energies of radiation, it is suggested to evaluate the energy response of the OSL signal from CaF2 detectors and its insertion in the developed algorithm.